Certainty - Rosmini, Antonio, 1797-1855. (Durham : Rosmini House, 1991)
Certainty develops the fundamental theory of knowledge already described by Rosmini in The Origin of Thought. The criterion of certainty, the force of a priori reasoning and the first division of the sciences are corollaries which spring immediately from Rosmini's recognition that the light of being, the first universal form of truth, is the objective, constitutive element of human intelligence.
Part one : the criterion of certainty -- Part two : application of the criterion to demonstrate the truth of pure knowledge -- Part three : application of the criterion to demonstrate the truth of non-pure, or materiated knowledge -- Part four : the errors to which human knowledge is subject -- Conclusion -- The forces present in priori reasoning -- The first division of the branches of knowledge.
"Translated from Nuovo Saggio sull'origine delle idee, vol. III."
Includes bibliographical references and indexes.
Keywords: Knowledge, Theory of